Structures hiérarchiques en terminologie - l 'hyperonymie - Kacprzak, Alicja (Wydawnictwo Naukowe UAM, 2001)
Along with antonymy and synonymy, hyperonymy is one o f the basic semantic relations in lexis. In specialistic terminologies the status of hyperonymy seems to be exceptional since this type o f vocabulary reflects the hierarchic character so typical for many fields o f science. This article presents the phenomenon o f hyperonymy in the language o f medicine in which it does not only perform the task o f ordering terminology, but is also an important factor which is a condition o f creation o f new terms.
Hierarchic structures in terminology - hyperonymy